Severe Headache as the Initial and Isolated Manifestation of a High-Volume Intracranial Meningioma: A Case Report - Makkiyah, Feda Anisah; Rizkyta, Bunga Mentari; Syahrin, Rosita Alfi; Sihotang, Theodora Caroline (Journal of Diverse Medical Research: Medicosphere, 2025)
Meningiomas are the most common benign intracranial tumors and make up 13-26% of all primary intracranial tumors. This tumor can be seen through radiological images and classified through the results of anatomical pathology examination. A 48-year-old woman came from Cileungsi Hospital with complaints of severe headaches in the past 3 days ago. When examined using a CT scan with contrast, an extra-axial mass was found in the right frontal region with prefocal edema around it. This supports the picture of high-grade meningioma which causes midline deviation towards the left. High-grade meningiomas, as one of the aggressive types of brain tumors, pose significant challenges in the fields of neurology and oncology. With its characteristic rapid growth and tendency to relapse, a thorough understanding of its diagnosis, treatment, and prognosis is essential in efforts to improve patient outcomes. This patient is scheduled for craniotomy surgery with a neurosurgeon specialist and found a tumor in the right parietal region with a solid consistency. with the patient's complaint lasting only 3 days, feeling severe headaches, it was found that the tumor image obtained was already large, making it is possible that the final outcome of the disease in these patients is poor due to delays in treatment. This case report shows that early detection of this disease needs to be done considering that the patient's complaints only lasted 3 days, which is not in line with the progression of the tumor itself.